2017
DOI: 10.1002/asi.23862
|View full text |Cite
|
Sign up to set email alerts
|

News stories as evidence for research? BBC citations from articles, Books, and Wikipedia

Abstract: Although news stories target the general public and are sometimes inaccurate, they can serve as sources of real-world information for researchers. This article investigates the extent to which academics exploit journalism using content and citation analyses of online BBC News stories cited by Scopus articles. A total of 27,234 Scopus-indexed publications have cited at least one BBC News story, with a steady annual increase. Citations from the arts and humanities (2.8% of publications in 2015) and social scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
3
4
1
Order By: Relevance
“…In contrast to the study of the United Kingdom by Kousha and Thelwall (2017) and Meyer (2018), there is no noticeable increase in the citations of media sources in this study over the years. It is possible, as Kousha and Thelwall (2017), Krtalic andHasenay (2012), andMeyer (2018) suggested, that media sources are more popular in certain fields compared to others. In fact, a study by Ravikumar and Agrahari (2015) and Singh and Ravikumar (2018a) also found that the media sources were not popular citation sources in the field of law.…”
Section: Citation Of Media By Law Studentscontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to the study of the United Kingdom by Kousha and Thelwall (2017) and Meyer (2018), there is no noticeable increase in the citations of media sources in this study over the years. It is possible, as Kousha and Thelwall (2017), Krtalic andHasenay (2012), andMeyer (2018) suggested, that media sources are more popular in certain fields compared to others. In fact, a study by Ravikumar and Agrahari (2015) and Singh and Ravikumar (2018a) also found that the media sources were not popular citation sources in the field of law.…”
Section: Citation Of Media By Law Studentscontrasting
confidence: 99%
“…It is clear from the results of this study that the media is the least cited information sources by law students. This finding is in agreement with previous studies in other domains that listed media sources among the least cited by TDs of students (Iroaganachi, Itsekor & Osinulu 2014;Kousha and Thelwall 2017). In contrast to the study of the United Kingdom by Kousha and Thelwall (2017) and Meyer (2018), there is no noticeable increase in the citations of media sources in this study over the years.…”
Section: Citation Of Media By Law Studentssupporting
confidence: 92%
See 1 more Smart Citation
“…To further illustrate our findings, we draw upon reliable media reports to explore and further understand attitudes, responses, and practice in the context of the significant numbers of COVID-19 related deaths. In order to ensure the validity of the media data, we only draw upon data from three trusted sources, namely BBC, ITV, and Sky News in alignment with academic analysis of digital news (Kousha and Thelwall, 2017 ; Newman et al, 2020 ). All media data used were cross-checked by both authors to ensure that any claims made were not disputed by the publicly available government data.…”
Section: Methodsmentioning
confidence: 99%
“…It is a marker to inform readers where an author's thought came from, guiding them to find out more relevant information (Case & Higgins, 2000). A citation also shows an author's decision to highlight other scholars' research work which is relevant to the argument in a particular paragraph (Case & Higgins, 2000;Kousha & Thelwall, 2017). In addition, it can contribute to an author's rhetoric in his or her research papers: persuading readers to agree with the argument by citing the sources.…”
Section: Cited Information In Research Papersmentioning
confidence: 99%